Pertanggungjawaban Direksi Atas Tindak Pidana Korporasi - Pardamean, Michael Christoper (Universitas Ekasakti, 2023)
Companies are legal entities (rechtspersoon) which are legal subjects other than humans. Just like humans, companies can also be subject to rights and obligations, and like humans too, companies can be held accountable if they are proven to have made mistakes and caused losses, including liability for criminal acts. The company in its business activities certainly does not operate alone. There is a management who becomes the